2011
DOI: 10.1016/j.jmb.2010.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR Structure of Apo-Calmodulin in Complex with the IQ Motif of Human Cardiac Sodium Channel NaV1.5

Abstract: The function of the human voltage-gated sodium channel Na V 1.5 is regulated in part by intracellular calcium signals. The ubiquitous calcium sensor protein calmodulin (CaM) is an important part of the complex calcium-sensing apparatus in Na V 1.5. CaM interacts with an IQ motif in the large intracellular C-terminal domain of the channel. Using co-expression and copurification, we have been able to isolate a CaM-IQ motif complex and to determine its highresolution structure in absence of calcium using multi-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
123
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(143 citation statements)
references
References 69 publications
15
123
0
1
Order By: Relevance
“…Data in Fig. 4A show that apo-CaM interacts with the IQ domain (residues 1896-1924) through its C lobe only, consistent with recent data (29). These interactions maintained the same profile and thermodynamic parameters with the C-terminal domain (CTD) spanning the EF hand and IQ domain (residues 1773-1925) (Table S4).…”
Section: Diii-iv Linker Is the Physiological Endpoint For Casupporting
confidence: 87%
See 2 more Smart Citations
“…Data in Fig. 4A show that apo-CaM interacts with the IQ domain (residues 1896-1924) through its C lobe only, consistent with recent data (29). These interactions maintained the same profile and thermodynamic parameters with the C-terminal domain (CTD) spanning the EF hand and IQ domain (residues 1773-1925) (Table S4).…”
Section: Diii-iv Linker Is the Physiological Endpoint For Casupporting
confidence: 87%
“…The C terminus of sodium channels contains two regions capable of conferring Ca 2+ -dependent modulation of inactivation, an EF-hand domain and a distal IQ motif. In the absence of Ca 2+ , the apo-CaM C lobe binds to the IQ motif of neuronal (30,32,33) and cardiac isoforms (5,6,8,29,30,34). Introduced or inherited mutations to either EF hands or IQ motifs can abolish Ca 2+ -dependent effects on inactivation (6,7,11,28); however, the ability of the EF-hand region to bind Ca 2+ ions directly remains contentious (7,8,11,28,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cav1.4 IQ motif (residues 1579 -1605) binds tightly to Ca 2ϩ -bound CaBP4 but not to Ca 2ϩ -free/Mg 2ϩ -bound CaBP4. Ca 2ϩ -dependent CaBP4 binding to IQ differs from the Ca 2ϩ -independent binding of IQ motifs to CaM (47,48) and other EF-hand proteins (55). The Cav1.4 IQ peptide binds to fulllength CaBP4 with at least 10-fold higher affinity than IQ binding to the individual lobes.…”
Section: Structure Of Cabp4 and Interaction With Cav14mentioning
confidence: 97%
“…7A, bottom right). The much higher affinity binding of the IQ peptide to CaBP4(100 -271) compared with the isolated lobes suggested that both lobes of Ca 2ϩ -bound CaBP4 bind cooperatively to the IQ peptide in contrast to apo-CaM (47,48), in which only the C-lobe forms contacts with the IQ motif.…”
Section: Structure Of Cabp4 and Interaction With Cav14mentioning
confidence: 99%